Register Now

222-9+11+12:2*14+14 = ? ( )

## Toán Lớp 6: Bài11 : Tìm x, biết. a. 2(x – 5) – 3(x + 7) = 14 b. 5(x – 6) – 2(x + 3) = 12 c. 3(x – 4) – (8 – x) = 12 d. -7(3x – 5)

Toán Lớp 6: Bài11 : Tìm x, biết.
a. 2(x – 5) – 3(x + 7) = 14
b. 5(x – 6) – 2(x + 3) = 12
c. 3(x – 4) – (8 – x) = 12
d. -7(3x – 5) + 2(7x – 14) = 28
e. 5(3 – 2x) + 5(x – 4) = 6 – 4x
f. -5(2 – x) + 4(x – 3) = 10x – 15

1. Giải đáp:
a) x = – 45
b) x = 16
c) x = 8
d) x = – 3
e) x = – 11
f) x = – 7
Lời giải và giải thích chi tiết:
Bài 11 :
a) 2 . ( x – 5 ) – 3 . ( x + 7 ) = 14
=> 2x – 10 – 3x – 21 = 14
=> 2x – 3x = 14 + 21 + 10
=> – x = 45
=> x = – 45
Vậy x = – 45
b) 5 . ( x – 6 ) – 2 . ( x + 3 ) = 12
=> 5x – 30 – 2x – 6 = 12
=> ( 5x – 2x ) – ( 30 + 6 ) = 12
=> 3x = 12 + 36
=> 3x = 48
=> x = 48/3 = 16
Vậy x = 16
c) 3 . ( x – 4 ) – ( 8 – x ) = 12
=> 3x – 12 – 8 + x = 12
=> 3x + x = 12 + 12 + 8
=> 4x = 24 + 8
=> 4x = 32
=> x = 32/4 = 8
Vậy x = 8
d) – 7 . ( 3x – 5 ) + 2 . ( 7x – 14 ) = 28
=> – 21x + 35 + 14x – 28 = 28
=> – 21x + 14x = 28 + 28 – 35
=> – 7x = 21
=> x = 21/(-7) = – 3
Vậy x = – 3
e) 5 . ( 3 – 2x ) + 5 . ( x – 4 ) = 6 – 4x
=> 15 – 10x + 5x – 20 = 6 – 4x
=> – 10x + 5x + 4x = 6 – 15 + 20
=> – x = 11
=> x = – 11
Vậy x = – 11
f) – 5 . ( 2 – x ) + 4 . ( x – 3 ) = 10x – 15
=> – 10 + 5x + 4x – 12 = 10x – 15
=> – 10 – 12 + 15 = 10x – 5x – 4x
=> – 7 = x
Vậy x = – 7

2. Đáp án:
a) 2. ( x-5) -3. (x+7)= 14
<=> 2x-10 -3x-21=14
<=> -x -31=14
<=> x=-31-14
<=> x=-45
b) 5(x-6)-2(x+3)=12
<=>5x-30-2x-6=12
<=>3x-36=12
<=>3x=48
<=>x=16
c) 5(x-6)-2(x+3)=12
<=>5x-30-2x-6=12
<=>3x-36=12
<=>3x=48
<=>x=16
d)
⇔-7(3x – 5) + 2(7x – 14) = 28
⇔-21x+35+14x-28=28
⇔-21x+14x+35-56=0
⇔-21x+14x-21=0
⇔-7x-21=0
⇔-7(x+3)=0
⇔x+3=0
⇔x=-3
e. 5(3 – 2x) + 5(x – 4) = 6 – 4x
⇒15-10x+5x-20=6-4x
⇒ 15-10x+5x-20-6+4x=0
⇒ -11-x=0
⇒ x=-11
F.5(2 – x) + 4(x – 3) = 10x – 15
<=> -10 +5x +4x -12 = 10x-15
<=> 5x+4x-10x= -15 +10 +12
<=> -x=7
<=> x=-7
#nocopy
Cho mik ctlhn với